Studying the four temperaments in medical hadiths of Ahl al-Bayt (AS) and comparing the results with temperament medicine - Abolfazl Saadati; Hasan Naghizadeh; Seyed Hosseyn Seyed Mosavi (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. Background and Objective: A major proportion of discussions in temperament medicine have to do with the four types of temperament, namely phlegmatic, melancholic, choleric, and sanguine. Similar titles can be detected in medical hadiths of Ahl al-Bayt (AS). The question is: Are the temperaments proposed in hadiths equivalent to the ones explicated in traditional medicine? The current study sought to answer this question. Method: Following an explanatory-comparative design, the study utilized content analysis to explain temperaments from the perspective of Ahl al Bayt's hadiths. The results were then compared with Hippocrates' ideas in traditional medicine. The research focused on reference books in hadiths and traditional medicine. All ethical issues were observed in this study and the researchers declared no conflict of interests. Results: The results indicated that, in hadiths, the term "temperament" refers to different mixtures of human body. The four mixtures of human body include rih, marrah, blood, and phlegm. No reference has been made to black bile and yellow bile in hadiths. On the other hand, some experts believe that black bile and yellow bile are subcategories of marrah. According to traditional medicine, the four elements of earth, water, air, and fire correspond to the four temperaments of melancholic, phlegmatic, sanguine, and choleric respectively. Also, another subtle material, known as vapor spirit, originates from the four temperaments. Conclusion: Based on the obtained results, there are similarities between what has been dubbed "four temperaments and vapor spirit" in traditional medicine and what has been discussed in medical hadiths about the body mixture of humans. For downloading the full-text of this article please click here.